STRATEGI KOPING DAN SELF-CARE TERHADAP KUALITAS HIDUP PENDERITA TUBERKULOSIS PARU - Mangelep, Jenori; Langelo, Wahyuny; Lumintang, Cyntia (Lasalle Health Journal, 2024)
Introduction: Pulmonary Tuberculosis (Pulmonary TB) is a disease that is transmitted from one person to another through direct contact with dust particles containing tuberculosis bacteria. A good coping strategy is needed for every pulmonary TB sufferer to undergo treatment in order to recover from the disease. Apart from the need to use good coping strategies, increasing Self-Care also has a big influence on the quality of life of pulmonary TB sufferers. Objective: This study aims to determine whether there is a relationship between coping strategies and Self-Care on the quality of life of pulmonary TB sufferers in the working area of the West Bitung Community Health Center. Method: This type of research uses non-experimental quantitative research with a correlation design. The research location was carried out in the working area of the West Bitung Community Health Center. The population in this study were pulmonary tuberculosis sufferers in the West Bitung Health Center Working Area with a sample size of 53 respondents suffering from pulmonary tuberculosis, the sample size of which was carried out using a non-probability sampling technique, namely purposive sampling. Results: It is known that pulmonary TB sufferers in the West Bitung Community Health Center work area have adaptive coping strategies and good Self-Care but have a poor quality of life. It can be concluded that the research hypothesis H0 is accepted and Ha is rejected. Conclusions: There is no relationship between coping strategies and Self-Care on the quality of life of pulmonary TB sufferers in the Bitung Community Health Center working area.